THE DESCRIPTION OF TEACHERS STRESSOR AND MANIFESTATION OF SPECIAL NEEDS TEACHERS IN INCLUSIVE AND SPECIAL SCHOOLS IN JAKARTA - Yapina Widyawati; Felicia Felicia (IJIET (International Journal of Indonesian Education and Teaching), 2017)
Teachers for special needs children are needed in inclusive and also in special schools (SLB). In inclusive schools, teachers who teach special needs children usually the class teacher or subject teacher. They usually have general pedagogic educational background. They were not specialized in teaching exceptional children. While on SLB, teacher had educational backgrounds from special education pedagogic. Both of them were dealing with different characteristics and their respective obligations demands. This situation could become a stressor that could affect learning. This research is a descriptive study. Characteristics of the sample in this study are that teachers who are between 20 and 65 years old, men and women, who teach at the elementary nation Inclusion and SLB. Participants obtained by the accidental sampling method were 67 people. Study showed that their stressor was from specific events relating to work. Source of their mild stress was setting time balance between personal time and work. A manifestation of stress occurs in the form of fatigue arising with regard to the perceived pressure. To reduce or minimize the stress that arises, necessary training and seminars to enrich their knowledge were needed, their also need good communication between the teacher and the school and build tolerance among co-workers.doi.org/10.24071/ijiet.2017.010107